Pengaruh Sudut Kaki Terhadap Kecepatan dan Sudut Simpangan Bola - Ulum, Muhammad Miftachul; Rubiono, Gatut; Sartika, Dewi (Virtual of Mechanical Engineering Article, 2019)
The research was conducted with experiments, with variations in the corners of the foot kick inside and outside. The angles used are 250and 350 w with foot swings of 450, 600 and 750. The result of this study showed that the greater the angle of the swing leg then the result of the leg swing against the ball would be faster the rate of the ball because the angle of a large leg swing would produce a large force or force. While the angle of the intersection of the foot is greater the angle of the resulting deviation will be the greater angle. The outer and foot kicks in differ as they kick using the straight leg of the ball will go straight by the pace of the balls whereas if using the outer foot will turn his ball or stray towards the specified kick.